STRATEGI UNIT PELAKSANA TEKNIS LATIHAN KERJA (UPTLK)WILAYAH II KOTA DUMAI DALAM PELAKSANAAN PENDIDIKAN DAN PELATIHAN - ", Firdaus; Tua R.F.S, Harapan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The high level of unemployment in Dumai City is of particular concern to the Dumai City Manpower Office. Job training is held and held to equip, improve, and develop work competencies in order to improve productivity and welfare capabilities. This study aims to determine the strategy of the Work Training Technical Implementation Unit (UPTLK) Region II of the City of Dumai in the implementation of education and training. This study uses the concept of theory quoting from Lawson (1977) in Rusdiana (2015), which explains that there are 3 strategies in the implementation of education and training namely strategies to increase knowledge, strategies to improve skills, and strategies to foster attitudes. The author uses qualitative research methods by analyzing the data descriptively. In data collection research uses interview, observation and documentation techniques. The results of this study can be seen that the strategy of the Work Training Technical Implementation Unit (UPTLK) Region II of the City of Dumai in the implementation of education and training is still not optimal, this can be seen from the problems found namely, the time of implementation of education and training is still lacking in improving the ability of the participants training, facilities and infrastructure in the implementation of education and training are still inadequate, and not yet in line with the plan and realization of training programs. This limitation has to do with the availability of budget and human resources. Keywords: Strategy, Unemployment, Education and Training